Село на пониззі Дніпра - Гудченко, З. (Народна творчість та етнографія, 2007)
The article is based on the author’s description of the village Sotnytske (Petrykivka District, Dnepropetrivsk Region), its environs, its history and people’s life there till the recent time. The researcher is studying the kinds of work and rest of the villagers, and some traditions of the housekeeping. The expedition was carried out in 1999, so we know not enough about the present conditions of this village, that is why these materials are particularly valuable. The researcher supplemented her descriptions with the sketches of the folk architecture performed with her own hand.